Controlling strategiczny w procesie kreowania zmian w systemie zarządzania przedsiębiorstwem - Nowosielski, Stanisław (Strategic controllership in the process of creating changes in the system of enterprise management, 2006)
The article shows deficiences of present controllership and its weak sides as the innovator of structural changes. It also indicates problems which have something in common with improving the system of planning. The possible ways of bringing this system to perfection were as well presented. The article also pays attention to the place which controllership takes when the new ideas of management are being introduced, and it shows the problems which can exist because of this situation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 328-337